PENDAMPINGAN PEMBELAJARAN BERBASIS METODE MONTESSORI BAGI GURU TK KANISIUS DEMANGAN BARU - Irine Kurniastuti; Andri Anugrahana; Albertus Hartana (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aimed to assist teachers at Kanisius Demangan Baru Kindergarten about Montessori method-based learning so that teachers can apply it in their respective classes. The method applied in this service is the discussion method by explaining the material to be delivered, the question and answer method is used to explore the teacher's understanding of the material to be given and the workshop is used to train and guide teachers in compiling learning videos that are integrated into the classroom. The results showed that the Montessori method of teaching mentoring received a positive response. The teacher clearly understood the material presented, especially the daily life skills area and the sensorial area. For language and mathematics materials, teachers need to get further assistance. The data result also explains that the Montessori method is effective and can be developed in Kanisius Kindergarten, Demangan Baru. In addition, the Montessori method is also relevant to the learning process and curriculum used by Kanisius Demangan Baru Kindergarten in collaboration with reflective pedagogy.